Small molecule inhibitors of bacterial transcription complex formation. Issue 18 (15th September 2017) - Wenholz, Daniel S.; Zeng, Ming; Ma, Cong; Mielczarek, Marcin; Yang, Xiao; Bhadbhade, Mohan; Black, David St. C.; Lewis, Peter J.; Griffith, Renate; Kumar, Naresh
Graphical abstract: Abstract: Knoevenagel condensation was employed to generate a set of molecules potentially capable of inhibiting the RNA polymerase- σ 70 / σ A interaction in bacteria. Synthesis was achieved via reactions between a variety of indole-7-carbaldehydes and rhodanine, N -allylrhodanine, barbituric acid or thiobarbituric acid. A library of structurally diverse compounds was examined by enzyme-linked immunosorbent assay (ELISA) to assess the inhibition of the targeted protein–protein interaction. Inhibition of bacterial growth was also evaluated using Bacillus subtilis and Escherichia coli cultures. The structure–activity relationship studies demonstrated the significance of particular structural features of the synthesized molecules for RNA polymerase- σ 70 / σ A interaction inhibition and antibacterial activity. Docking was investigated as an in silico method for the further development of the compounds.